LEADERSHIP KEPALA MADRASAH DALAM PENGEMBANGAN SUMBER DAYA MANUSIA (SDM) SEBAGAI UPAYA PENINGKATAN MUTU MADRASAH - Hamidi, M. Arwan (Jurnal Aspirasi, 2012)
The development of Islamic education, especially in Madrasah or Islamic school is needed to improve the quality of religious education. Madrasah is the representation of an implementation of a devoted Islam (kaffah), because Madrasah is believed to be able to integrate the religion and modern knowledge to the students. The best education will produce the best students too. This is reflected on the activities that students do in education process. The succed of the school’s principal in managing his educational institution is the key to successfully improve the quality of the school especially to develop human resources.